Research on adaptive impedance control technology of upper limb rehabilitation robot based on impedance parameter prediction - Zhang, Yuling; Li, Tong; Tao, Haoran; Liu, Fengchen; Hu, Bingshan; Wu, Minghui; Yu, Hongliu (Frontiers in Bioengineering and Biotechnology, 2024)
With the aggravation of aging and the growing number of stroke patients suffering from hemiplegia in China, rehabilitation robots have become an integral part of rehabilitation training. However, traditional rehabilitation robots cannot modify the training parameters adaptively to match the upper limbs’ rehabilitation status automatically and apply them in rehabilitation training effectively, which will improve the efficacy of rehabilitation training. The study aimed to develop an adaptive impedance strategy for upper-limb rehabilitation robots, enabling dynamic adjustments via impedance parameter prediction. The forgetting factor recursive least squares method (FFRLS) was utilized to estimate the impedance parameters of human upper limb end. A reward function was established to select the optimal stiffness parameters of the rehabilitation robot. The results from the experiments further confirmed the effectiveness of the adaptive impedance control strategy. The findings of the adaptive impedance control studies showed that the adaptive impedance control had a significantly greater reward than the constant impedance control, which was in line with the simulation results of the variable impedance control. Besides, it was observed that the levels of robot assistance could be suitably modified based on the subject’s different participation. This facilitated stroke patients' upper limb rehabilitation by enabling the rehabilitation robot to adaptively change the impedance parameters according to the functional status of the affected limb. In clinic therapy, the proposed control strategy may help to adjust the reward function for different patients to improve the rehabilitation efficacy eventually.